Ambiguities of care in Alzheimer's disease: To care/become a caregiver by obligation or by the charity - Luana Machado Andrade; Luma Costa Pereira Peixoto; Lucio Silva Sena; Patrícia Anjos Lima de Carvalho; Luciana Araújo dos Reis; Edite Lago da Silva Sena (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Objective: To understand the meaning of the ambiguities of being a caregiver experienced by family caregivers of people with Alzheimer's disease and health workers inserted in community Mutual Help Groups. Method: a study based on the ontology of Maurice Merleau-Ponty's experience based on the notion of the body itself. It is revealed by the participation of 12 women, family caregivers, and health workers, members of community mutual aid groups, in the city of Jequié, Bahia, Brazil. The production of the experiential descriptions took place in three Focus Group meetings, during April and December 2019, whose resulting material was submitted to the Ambiguity Analysis.  Results: The results reveal the ambiguities of taking care mobilized by the tradition of fulfilling social, cultural, and religious duties. Inserted in the groups, they experience openness to the other, reconfiguring "doing for doing" in "doing for pleasure" in care practices, becoming another.  Conclusion: the experience of caring as an obligation, which was previously expressed by anguish, sadness, and illness, after insertion in the group, opens up to the experience of the other and makes care a manifestation of otherness, which privileges the care of the self to care from the other. The study points out the group strategy in health services as a possibility of transforming social actors in the community in the context of Alzheimer's disease.